Hubungan Mutu Pelayanan Kesehatan Dengan Kepuasan Pasien Rawat Inap Diruang Bedah RSUD Mayjen H.A Thalib Kota Sungai Penuh Tahun 2025 - Moza Suzana (Universitas Sumatera Barat, 2026)
The existence of health is very important in realizing a healthy society, various government and private health services are established in each region to facilitate the community in accessing health services. The purpose of this study is to determine the reciprocal relationship between health services and inpatient satisfaction in the Surgical Room of Mayjen H.A Thalib Regional General Hospital, Sungai Penuh City in 2025. This type of research is quantitative and analytical with a cross-sectional study approach. The independent variable in this study is the quality of health services, while the dependent variable is inpatient satisfaction. The population in this study were all patients treated in the Surgical Room of Mayjen H.A Thalib Regional General Hospital, Sungai Penuh City in 2024, the population consisted of 1033 people with a sample of 91 people. The sampling technique used in this study was the Accidental Sampling technique. This research was conducted in the Surgical Room of Mayjen H.A Thalib Regional General Hospital, Sungai Penuh City. The research time was conducted in January-June 2025. The results showed that most of the 46 (50.5%) respondents with good quality of health services, most of the 52 (71.1%) respondents with a satisfied level of satisfaction, with the results of the statistical test (Chi Square) obtained a p value of 0.004. The conclusion in this study is to show that there is a reciprocal relationship between health services and the satisfaction of inpatients in the Surgery Room of Mayjen H.A Thalib Regional General Hospital, Sungai Penuh City in 2025. The suggestion of this study is that it can be applied in daily care practices such as providing good reciprocal services, so that patients will always be satisfied with the services provided by nurses.